KONTRIBUSI HIMABIWA DALAM PENGABDIAN KEPADA MASYARAKAT MELALUI BAKTI SOSIAL DI KALURAHAN BANYURADEN - Hadi, Antonius Satria; Sari, Utami Tunjung; Artha, Bhenu; Bahri, Bahri; Sari, Niken Permata; Asri, Cahya Purnama; Ardi, Ardi (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community service activities play a crucial role in fostering social awareness and student engagement in improving community welfare. This community service activity promoted the contribution of students in enhancing community welfare through a food-sharing social service program conducted by HIMABIWA. The program aims to provide food assistance to underprivileged communities while fostering a spirit of empathy and social responsibility among students. This paper analyzed the program's impact through direct observation and quick interviews with beneficiaries. The findings indicate that this initiative not only provides immediate food relief but also strengthens social bonds between students and the community. Furthermore, the program enhances students' understanding of real-world social issues and encourages active participation in humanitarian efforts. This study highlights the significance of student involvement in social programs as a means of holistic education, bridging academic knowledge with practical social contributions. The results suggest that structured and sustainable social initiatives can serve as an effective model for student-community engagement and social solidarity.